2004
DOI: 10.1111/j.1083-4389.2004.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori Eradication on Platelet Activation and Disease Recurrence in Patients with Acute Coronary Syndromes

Abstract: Infection with H. pylori does not induce significant platelet activation in patients treated for coronary disease. Helicobacter pylori-infected patients, however, may have an increased risk of recurrence of coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
3
23
1
1
Order By: Relevance
“…Our observation of decreased platelet CD62p expression contrasts with those of Elizalde et al [17] who studied patients with acute coronary syndromes but were unable to identify elevated platelet CD62p expression in patients with H. pylori infection or a reduction in expression following eradication therapy compared with placebo-treated controls. Since all patients were treated for acute coronary syndromes, anti-platelet medications were probably a confounding factor, and the authors acknowledge this possibility in their discussion (one third of the patients were on both clopidogrel and aspirin, and almost all were on aspirin).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observation of decreased platelet CD62p expression contrasts with those of Elizalde et al [17] who studied patients with acute coronary syndromes but were unable to identify elevated platelet CD62p expression in patients with H. pylori infection or a reduction in expression following eradication therapy compared with placebo-treated controls. Since all patients were treated for acute coronary syndromes, anti-platelet medications were probably a confounding factor, and the authors acknowledge this possibility in their discussion (one third of the patients were on both clopidogrel and aspirin, and almost all were on aspirin).…”
Section: Discussioncontrasting
confidence: 99%
“…The potential impact of aspirin and clopidogrel on CD62p expression studies on patients with atherosclerosis is also suggested in a study by Klinkhardt et al [25] who demonstrated that CD62p expression was lower in patients on aspirin or clopidogrel compared with controls, although the clopidogrel group was alone in reaching statistical significance. However, Elizalde et al [17] did find that only final H. pylori infectionstatus and coronary risk factors predicted recurrence of cardiovascular events. Our patient population is uniquely favorable to study the effect of H. pylori eradication on platelet CD62p expression, since patients are uniformly advised to avoid anti-platelet therapy due to the hemorrhagic risk associated with low platelet counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to the relation between HP infection and stroke, positive 12) and negative 13) test results have been reported. It has also been reported that the eradication of HP and antibiotics against HP reduced the recurrence rate of acute coronary events 14,15) . Arterial stiffness is an independent and impor-…”
mentioning
confidence: 94%
“…36 In addition, H pylori eradication is associated with a reduction of secondary coronary events in patients with CVD. 37 In the South Thames Trial of Antibiotics in Myocardial Infarction and Unstable Angina (STAMINA) trial, a significant reduction in C-reactive protein and improvement in event-free survival was reported with combined treatment for both C pneumoniae and H pylori. 38 However, data from experimental mouse models with C57Bl/6, LDL receptor (LDLR) −/− , or ApoE −/+ and LDLR −/+ mice are controversial and inconclusive.…”
Section: Bacteriamentioning
confidence: 99%